2020
DOI: 10.1159/000508321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Glucocorticoid Replacement Regimens Used in Chronic Adrenal Insufficiency: A Systematic Review

Abstract: Objective: Patients with adrenal insufficiency require life-long glucocorticoid replacement therapy. Hydrocortisone (15–30 mg/day) and prednisolone (3–7.5 mg/day) are the preferred agents used although there is a lack of consensus among endocrinologists regarding the impact of different steroid regimens on quality of life, bone metabolism, cardiometabolic outcomes, adrenal crisis and infections. We carried out a retrospective systematic review of the literature to compare the efficacy and side effects of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Hydrocortisone is the most commonly administered glucocorticoid therapeutic agent for adrenal insufficiency. Clinic data from the UK revealed 72% of patients were managed with hydrocortisone, 26% with prednisolone and 2% with modified release hydrocortisone [9]. Data from the European Adrenal Insufficiency Registry.…”
Section: Glucocorticoid Replacementmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrocortisone is the most commonly administered glucocorticoid therapeutic agent for adrenal insufficiency. Clinic data from the UK revealed 72% of patients were managed with hydrocortisone, 26% with prednisolone and 2% with modified release hydrocortisone [9]. Data from the European Adrenal Insufficiency Registry.…”
Section: Glucocorticoid Replacementmentioning
confidence: 99%
“…In clinical practice the use of hydrocortisone or prednisolone are often preferable due to their more predictable pharmacokinetics compared to their precursor hormones cortisone and prednisone [9]. The normal functioning adrenal glands are thought to produce 5-10 mg cortisol per m 2 body surface area/per day; this equates to an oral hydrocortisone dose of 15-25 mg/per day for an adult [11].…”
Section: Glucocorticoid Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean replacement dose reported in their study was 7.6 ± 3.5 mg/m2, reflecting daily endogenous cortisol production (72). A recent systematic review of 47 studies reported that although prednisolone therapy increased risk of dyslipidemia and cardiovascular disease, it was as safe and efficacious as hydrocortisone (73). It also suggested that lower doses of hydrocortisone (less than 20 mg/day) had better clinical outcomes, and failed to conclusively demonstrate an added benefit of modified release hydrocortisone or continuous subcutaneous hydrocortisone infusion using insulin pumps (73).…”
Section: Management Of Chronic and Acute Paimentioning
confidence: 95%
“…A recent systematic review of 47 studies reported that although prednisolone therapy increased risk of dyslipidemia and cardiovascular disease, it was as safe and efficacious as hydrocortisone (73). It also suggested that lower doses of hydrocortisone (less than 20 mg/day) had better clinical outcomes, and failed to conclusively demonstrate an added benefit of modified release hydrocortisone or continuous subcutaneous hydrocortisone infusion using insulin pumps (73). Current available regimens fail to replicate both circadian and ultradian rhythmicity of cortisol, potentially explaining the persistently low quality of life that patients with AI often complain about.…”
Section: Management Of Chronic and Acute Paimentioning
confidence: 99%